Impact of Temperature Change on the Fall Armyworm, Spodoptera frugiperda under Global Climate Change - Xiao-Rui Yan; Zhen-Ying Wang; Shi-Qian Feng; Zi-Hua Zhao; Zhi-Hong Li (Insects, 2022)
The fall armyworm (FAW), Spodoptera frugiperda (J. E. Smith, 1797), known as an important agricultural pest around the world, is indigenous to the tropical–subtropical regions in the Western Hemisphere, although its distribution has expanded over large parts of America, Africa, Asia and Oceania in the last few years. The pest causes considerable costs annually coupled with its strong invasion propensity. Temperature is identified as the dominant abiotic factor affecting herbivorous insects. Several efforts have reported that temperature directly or indirectly influences the geographic distribution, phenology and natural enemies of the poikilothermal FAW, and thus may affect the damage to crops, e.g., the increased developmental rate accelerates the intake of crops at higher temperatures. Under some extreme temperatures, the FAW is likely to regulate various genes expression in response to environmental changes, which causes a wider viability and possibility of invasion threat. Therefore, this paper seeks to review and critically consider the variations of developmental indicators, the relationships between the FAW and its natural enemies and the temperature tolerance throughout its developmental stage at varying levels of heat/cold stress. Based on this, we discuss more environmentally friendly and economical control measures, we put forward future challenges facing climate change, we further offer statistical basics and instrumental guidance significance for informing FAW pest forecasting, risk analyses and a comprehensive management program for effective control globally.